(3Sdhc GdeSJgdc (B: s (3ehLgI dWdHI GdSfI GdKGdKI djSGfS (B: (3JNUU JShjb (B/ s - (3HQHGQI,OdjdIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2023)
(3eONd YGe ddJShjb,eONd YGe dSdhc GdeSJgdc,GdfeGPL GdeaSQI dSdhc GdeSJgdc,GdYhGed GdOGNdjI GdfaSjI GdeDKQI Ydi Sdhc GdeSJgdc,GdYhGed GdNGQLjI GdeDKQI Ydi Sdhc GdeSJgdc GdYhGed GdGbJUGOjI h GdJShjbjI,GdYhGed GdNGQLjI GdeDKQI Ydi Sdhc GdeSJgdc GdYhGed GdELJeGYjI,GdYhGed GdNGQLjI GdeDKQI Ydi Sdhc GdeSJgdc GdYhGed GdKbGajI,GdYhGed GdNGQLjI GdeDKQI Ydi Sdhc GdeSJgdc GdYhGed GdehbajI,bQGQ GdTQGA(B.s
(3eQGLY U(B.125s
Keywords: (3Sdhc GdeSJgdcs